Neurological effects in workers exposed to toluene. Systematic review (Medicina y Seguridad del Trabajo, 2022)
Introduction and objective: toluene is an organic solvent derived from benzene used in various industries, with potential harmful effects for workers. This study aims to determine the possible neurological effects of workers exposed to toluene.Material and methods: Systematic review of studies published in English and Spanish between January/2000-December/2021. The databases consulted were MEDLINE, WOS, Scopus, Embase, LILACS, IBECS and Cochrane Library. Study quality was assessed using the STROBE statement and the level of evidence using the SIGN criteria.Results: 14 observational studies were included (quality between 13-18, level of evidence between 2+ and 3). Eight studies examined non-specific neurological symptoms and behavioral alterations, finding an increase in symptoms such as headache, nausea or vomiting, and a decrease in motor performance and attention in workers exposed to toluene (p
Keywords: toluene; occupational exposure; neurological effects; color vision defects; hearing loss